Social Economic Background of Families’ Sport Habits (Training and Practice : Journal of Educational Sciences, 2017)
This study focuses on the role of certain factors responsible for physical and mental health, paying particular attention to the relationship between the family and physical education.In our article we show and examine the role of leasure activities and sport in connection with 3 generations. We examine the social economic aspect of this topic.The study was carried out in Hungary, in the North-Hungarian region, among 10-14-year-old children, their parents and grandparents, we analysed 2036 questionnaires, and 150 interviews in structured forms.